Observation of autoionization dynamics and sub-cycle quantum beating in electronic molecular wave packets. (23rd February 2016) - Reduzzi, M; Chu, W-C; Feng, C; Dubrouil, A; Hummert, J; Calegari, F; Frassetto, F; Poletto, L; Kornilov, O; Nisoli, M; Lin, C-D; Sansone, G
Abstract: The coherent interaction with ultrashort light pulses is a powerful strategy for monitoring and controlling the dynamics of wave packets in all states of matter. As light presents an oscillation period of a few femtoseconds ( T  = 2.6 fs in the near infrared spectral range), an external optical field can induce changes in a medium on the sub-cycle timescale, i.e. in a few hundred attoseconds. In this work, we resolve the dynamics of autoionizing states on the femtosecond timescale and observe the sub-cycle evolution of a coherent electronic wave packet in a diatomic molecule, exploiting a tunable ultrashort extreme ultraviolet pulse and a synchronized infrared field. The experimental observations are based on measuring the variations of the extreme ultraviolet radiation transmitted through the molecular gas. The different mechanisms contributing to the wave packet dynamics are investigated through theoretical simulations and a simple three level model. The method is general and can be extended to the investigation of more complex systems.